The ‘Humanitarianisation’ of civil society : Legal tensions, unaccompanied youth and homelessness in Malmö - Solano, Priscilla (Nordic Journal of Social Research, 2024)
This article highlights the restructuring of the Swedish welfare state through looking at how a humanitarian logic has entered civil society at a local level around the issue of precarious housing for unaccompanied youth. Drawing on existing literature on ‘humanitarian reason’ (Fassin 2011) and ‘humanitarian citizenship’ (Cabot 2019), the article explores the 2019 ‘crisis’ affecting unaccompanied youth as they turned 18, and how civil society morphed into emergency organisations in Malmö, Sweden. Focus is specifically centred on shifts in law and policy, and rewritten guidelines that limit access to housing support. As responsibility for issues such as homelessness are displaced onto the individual by social services, the article argues that the situation of housing as humanitarian for unaccompanied youth is yet another symptom of the erosion of the social democratic welfare state in Sweden.